The complete chloroplast genome sequence of Callitriche palustris (Plantaginaceae) - Jiaojun Yu; Hongjin Dong (Mitochondrial DNA. Part B. Resources, 2021)
Callitriche palustris L. is an annual aquatic or marsh plant, wide spread in temperate regions throughout the world. In present study, we sequenced, assembled and annotated the complete chloroplast (cp) genome of C. palustris. The length of C. palustris complete cp genome was 150,138 bp, with a typical quadripartite structure comprising a pair of inverted repeat regions (IRs; 25,667 bp), a large single copy region (LSC; 81,432 bp) and a small single copy region (SSC; 17,372 bp). The whole cp genome contained 134 genes, including 89 protein-coding genes (PCGs), 37 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. The maximum likelihood (ML) phylogenetic analysis indicated that C. palustris was a member of Plantaginaceae, but the relationships between subfamilies and tribes need more samplings. This cp genome would provide a valuable genetic resource for C. palustris’ phylogenetic study.